EDUKASI PENINGKATAN PERAN KELOMPOK CERDIK DALAM PENCEGAHAN STROKE DI WILAYAH KERJA PUSKESMAS KEBUN SIKOLOS PADANG PANJANG - Lilisa Murni; Ida Suryati; Maidaliza Maidaliza (Universitas Pahlawan Tuanku Tambusai, 2022)
In early 2018, the UPTD of Kebun Sikolos Health Center made an innovation by establishing a Smart Group, namely the development of the Serambi Prolanis Group. The management of this group was modified so that the activities did not only focus on medical consultations, home visits, reminders, group activities and monitoring of health status, but were also developed into agents providing information, promotion and health education in the neighborhood. The goal is to encourage participants with stroke to achieve optimal quality of life. This ingenious group consists of 200 people and not all of the elderly here have good behavior in preventing stroke, including smoking and consuming fatty foods. This Smart Group has attended training conducted by community nurses on stroke elderly aggregates to help community groups learn new knowledge and skills related to stroke care and provide encouragement to group members. The purpose of community service is to increase the role of the Smart group in terms of motivation, health promotion and stroke prevention efforts through the provision of comprehensive education. The results of pre and post tests regarding the knowledge of members of the smart group related to their role in stroke prevention were very good. Conclusions and suggestions for good behavior in stroke prevention in the UPTD Working Area of ??Kebun Sikolos Health Center Padang Panjang can be realized through education to increase the role of smart groups about understanding and good application of motivation, communication, acting as role models, prioritizing educational goals for families, neighbors and communities in residential environment and the general public as well as ways to prevent stroke. Keywords: smart group, participation, stroke prevention behavior